Parhyale darvishi, a new widely distributed amphipod species, in the Persian Gulf and the Gulf of Oman (Crustacea, Amphipoda, Hyalidae) - Momtazi, Farzaneh; Maghsoudlou, Abdolvahab (Zootaxa, 2016)
Parhyale darvishi sp. nov., is described. The new species is characterized by a naked posterior margin on the propodus of pereopods 5–7, a special arrangement of robust setae on the first male gnathopod and a lack of dense fine setae on the second antennae. Parhyale darvishi sp. nov. is distributed from the western coasts of the Persian Gulf to the eastern coasts of Gulf of Oman.